2000
DOI: 10.1074/jbc.275.16.12290
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Binding Characteristics of the Androgen and Glucocorticoid Receptors Can Determine Hormone-specific Responses

Abstract: The basis for specificity of gene regulation by steroid hormone receptors remains an important problem in the study of steroid hormone action. One possible mechanism for steroid specificity is the difference in DNA binding characteristics of the receptors, although they share a high homology in their DNA-binding domains. Indeed, the androgen-specific expression of, for example, the probasin (PB) gene can be explained by the presence of an androgen response element (ARE) in its promoter (PB-ARE-2), specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 50 publications
3
65
1
1
Order By: Relevance
“…Because cooperative dimerization greatly increases the affinity of receptors for their bipartite response elements, these two changes should also increase the relative affinity of the AR for a given response element compared with GR. In support of this hypothesis, GR DBD mutants containing a serine in place of Gly-478 [39] in the D box or a threonine in place of GR Ile-483 [44] show increased affinity for both palindromic and direct-repeat response elements compared with wild type (34), confirming the importance of these interactions for dimer stability.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Because cooperative dimerization greatly increases the affinity of receptors for their bipartite response elements, these two changes should also increase the relative affinity of the AR for a given response element compared with GR. In support of this hypothesis, GR DBD mutants containing a serine in place of Gly-478 [39] in the D box or a threonine in place of GR Ile-483 [44] show increased affinity for both palindromic and direct-repeat response elements compared with wild type (34), confirming the importance of these interactions for dimer stability.…”
Section: Resultssupporting
confidence: 59%
“…All the steroid receptors (MR, PR, GR, and AR) show a 5-to 10-fold lower affinity for the naturally occurring PB-ARE-2 DR3-type element than the C3 (1) IR3-type element (34). However, the AR DBD binds 3-to 10-fold better to both elements relative to the other steroid receptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HRE flanking and spacer DNA can contribute to the affinity and specificity of receptor binding (Nelson et al, 1999). The DBD of androgen receptor (AR) has lower (76%) homology with the GR DBD (Chang et al, 1988), which seems to be sufficient for DNA binding specificity of AR vs. GR (Massaad et al, 2000;Schoenmakers et al, 2000). Thus subtle differences in HRE sequence may regulate the relative activities of GR and PR (Thackray et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Selective DNA binding by the AR could be one possible mechanism for hormone-specific gene regulation. It has been reported that the AR-DBD does not only recognize response elements organized as inverted repeats of 5Ј-TGTTCT-3Ј sequences with a threenucleotide spacer but can also bind to direct repeats of 5Ј-TGTTCT-3Ј-like sequences, which is proposed to contribute to the AR specificity of transcriptional responses (7)(8)(9)(10)(11)(12)(13)(14). The NTD of the AR is indispensable for AR transactivation and contains a strong transcription activation function (AF-1).…”
mentioning
confidence: 99%